Editorial - Gachago, Daniela (Critical Studies in Teaching and Learning, 2023)
This is the first issue published by CriSTaL since I became the managing editor early this year. When I was asked whether I would consider taking over from Dr Sherran Clarence, I was excited and not just a little bit daunted. I have followedCriSTaL’s journey from a (close) distance, observing its a  mazing growth, gaining accreditation, and increasing its yearly issues. My own work is positioned in a critical feminist paradigm and CriSTaL has always been close to my heart.